Theoretical and experimental studies of polarized infrared reflectance of bulk wurtzite ZnO semiconductor - Lee .S.C,; Ng .S.S,; Hassan .Z,; Abu Hassan .H, (Universiti Kebangsaan Malaysia, 2011)
Polarized infrared (IR) reflectance spectrum studies of bulk wurtzite ZnO are presented. The features of the polarized IR reflectance spectra and the optical characteristics of ZnO were investigated. Based on the anisotropic dielectric function model, the experimental IR reflectance spectra were numerically fitted by the theoretical IR reflectance spectra. The obtained transverse optical (TO) and longitudinal optical (LO) frequencies, i.e., ωTO⊥(ωTO||) and ωLO⊥(ωLO|| ) are 411 cm-1 (384 cm-1) and 589.8 cm-1 (572 cm-1), respectively. These results are compared with the reported values measured from the other techniques. Good agreement has been obtained.